Digital nation : toward an inclusive information society - Wilhelm, Anthony G. (MIT Press, 2004)
The long-term social benefits of building an inclusive information society: a national action plan. As our social institutions migrate into cyberspace, the digitally disenfranchised face increasing hardships. What happens when--in search of quick and cheap fixes--a government office shuts down and is replaced by a public Web site? What happens when a company accepts only online job applications? Inevitably, those most in need of the services and opportunities offered are further marginalized. In Digital Nation, Tony Wilhelm shows us how to build a more inclusive information society, offering a plan that reaps the benefits offered by the new technology while avoiding the pitfalls of social exclusion. Technology, he tells us, isn't the problem--it's the use of technology that can empower or control, unite or divide; we need to recover the ideas of social justice and fairness that have been lost in the rush to make things faster and cheaper. In Wilhelm's vision of an inclusive digital nation, everyone can take advantage of the new technology. With everyone part of the information society, we can revolutionize the way we educate our citizens, deliver healthcare, and engage in productive work. The result will be increased efficiency and productivity that will lead to long-term savings of billions of dollars and an enhanced quality of life as technology expands choice and opportunity. We can begin to bring this about by expanding access to computers and making it easier to acquire digital literacy skills. To do nothing--to turn a blind eye to the promise of an inclusive technology--would cost us socially and economically. Digital Nation's call for action sets the terms for a new debate on bridging the digital divide.